Analisis Rantai Pasok Produk Beras dari Kabupaten Konawe Selatan ke Kota Kendari - Armansyah, Armansyah; Abdullah, Bahari; Zani, Munirwan (Department of Agribusiness, Halu Oleo University, 2019)
This study aims to find out how the supply chain of rice from South Konawe to Kendari. This type of research is included in descriptive research or categorized in qualitative research method by using survey method that is described, explain and interpret a phenomenon that occurs on an object and data is qualitative, ie data that is described with words or sentences by category to obtain a conclusion. This research was conducted in South Konawe Village specifically at UD. Fandi in Laeya District, South Konawe District in August 2017. Data collection techniques were conducted through observation, interviews, discussions with supply chain members and documentation at the research sites. Supply Chain of rice products from South Konawe District to Kendari City starts from Farmers, Rice Millers, Distributors UD Fandi, Retailer and Final Consumer. Farmers as rice suppliers cultivate and sell their crops to the rice mills, then the mills' process rice from farmers into rice products to be sold to Distributor. In this research, the Distributor Party also as the owner of rice milling, after the packaging of rice products, will then be distributed to retailers both in South Konawe District itself and outside the region, especially Kendari City distributor of UD. Fandi has a rice warehouse which is a shelter of rice products that will be sold to retailers in Kendari City. The selling price of rice products from Distributor UD. Fandi is accepted by retailers in South Konawe and outside Kendari especially divided by size, for rice with size 50 kg sold with price Rp. 420.000, - and for rice with size 25 kg sold with price Rp. 220.000, Furthermore the retailers will repackage the rice products into several sizes that are tailored to the needs of the end consumer is the size of 10 kg, and size 5 kg. for rice with size 10 kg sold with price Rp. 110.000, - and rice with size 5 kg sold with price Rp. 55.000, -. But retailers also sell rice with liter sizes which for liters sold to consumers at a price of Rp. 8,000-8,500, / litres. This is done to adjust to the level of end consumer needs.